2019
DOI: 10.1186/s12879-019-3840-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and the effects of weather on Campylobacter infections

Abstract: BackgroundCampylobacteriosis is a major public health concern. The weather factors that influence spatial and seasonal distributions are not fully understood.MethodsTo investigate the impacts of temperature and rainfall on Campylobacter infections in England and Wales, cases of Campylobacter were linked to local temperature and rainfall at laboratory postcodes in the 30 days before the specimen date. Methods for investigation included a comparative conditional incidence, wavelet, clustering, and time series an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…We applied the negative binomial harmonic regression NBHR models, commonly used in the time series analysis of counts and cases. While the use of NBHR models, specifically the inclusion of trigonometric harmonic oscillations, is similar to existing works on foodborne illnesses, these studies often incorporate harmonic oscillators only to adjust for or remove seasonal oscillations [47][48][49][50][51][52][53][54][55] . We have extended the use of harmonic terms and develop the tools to estimate peak timing and amplitude 8,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…We applied the negative binomial harmonic regression NBHR models, commonly used in the time series analysis of counts and cases. While the use of NBHR models, specifically the inclusion of trigonometric harmonic oscillations, is similar to existing works on foodborne illnesses, these studies often incorporate harmonic oscillators only to adjust for or remove seasonal oscillations [47][48][49][50][51][52][53][54][55] . We have extended the use of harmonic terms and develop the tools to estimate peak timing and amplitude 8,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Only few published studies have analysed the association between climate and Campylobacter cases-and some with conflicting results. Generally, it appears that Campylobacter in chicken flocks fluctuates with temperature and humidity 9,44 while incidences in humans may be linked to fluctuations in both temperature and rainfall and especially heavy precipitation events 21,24,25,28,[45][46][47][48] . Heat waves have been linked to reduced incidences of Campylobacter 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 30, 2021. ; https://doi.org/10.1101/2021.03.30.437710 doi: bioRxiv preprint BROILER WELFARE AND CAMPYLOBACTER with the warmer, summer months seeing flocks test positive for Campylobacter more frequently (Djennad et al, 2019;Nylen et al, 2002).…”
Section: /38mentioning
confidence: 99%
“…Previous studies have suggested that the seasonal increase of flies (Hald et al, 2004(Hald et al, , 2007, rodents (Meerburg and Kijlstra, 2007), and wild birds (Colles et al, 2008) as vectors of Campylobacter transmission may be responsible, while seasonal patterns in country-wide clonal complex incidence potentially point to genetic adaptation to seasonal trends (Jorgensen et al, 2011). Investigating this trend in human incidence of campylobacteriosis, Djennad et al (2019) conducted a rigorous statistical assessment of spatial and weather factors, concluding that the correlation between incidence and temperature was " likely to be indirect". Our above results reach the same conclusion for broiler colonization.…”
Section: /38mentioning
confidence: 99%